A avaliação na voz dos profissionais da educação: a experiência do município de Paulínia/SP - Ribeiro, Thainá Portela Rêgo [UNESP] (2015)
Evaluation is a gift in the school category and educational policies from the 90s and thus, it is very present in the organization of educational work in schools, in the classroom, the teacher's work.This paper intends to study on educational assessment within a municipal project, and look for the evaluation from the perspective of teachers and managers from aa reflection on the evaluation and review of the act. This research aims to investigate the concept of evaluation in this proposal the curriculum of the city of Paulinia / SP, considering the assessment as an essential part of the teaching-learning process, the pedagogical work in an attempt to student education in its fullest sense. In the proposal the curriculum of Paulinia Network, the evaluation comes first in the organization of the pedagogical work, in which first evaluates to then plan and execute the objectives of two months. It is a qualitative research, which was used in literature related to the study of research theme, the evaluation. Semi-structured interviews with three managers of the study proposal, and a teacher representative from each school were held, totaling 22 teachers in an attempt to capture the understanding of the assessment that permeated the construction and implementation of the proposed Paulínia/SP. The entire project was significant and relevant as training process for participating teachers as it allowed the teachers to look at their action, their practice, and to review this practice, looking at the student itself and its difficulties, the obstacles toThey are faced and how to work with this student. The evaluation process that took place in the preparation of Curriculum Network allowed that all the work done by the proposal evaluation allowed the project participants a fresh look at the evaluation and a new action before the pedagogical process